Leveraging GIS for Empowering Health Research in Pakistan: A Path to Smarter Public Health Solutions - Masood Ali Shaikh; Syed Muhammad Mubeen (Journal of the Pakistan Medical Association, 2025)
Location is a fundamental feature for understanding theoccurrence, spread of diseases and their associated riskfactors. Understanding that "everything that happens,happens somewhere"1 underscores the essentialsignificance of geography in the analysis of health anddisease morbidity and mortality burdens. Epidemiology isall about understanding the interaction of place with timeand individual characteristics to fathom the distributionand determinants of diseases. This spatial standpoint isimperative for a nuanced understanding of how varioussocial, economic, biological, and environmental factorsintertwine to influence and confluence health outcomes.Spatial analysis offers insights into the distribution andclustering of diseases across space, hot and cold spotidentification, and uncover spatial variations in healthbehaviours and outcomes. Providing pivotal context forthe effective prevention, control, and management ofdiseases by providing spatial context for targettedinterventions and policies to specific geographical areas.Contrary to cookie-cutter solutions based on theerroneous assumption of one-size-fits-all. Continues...